Autistic Students within the Community of Inquiry - Garwood, Rylan (Stance: an international undergraduate philosophy journal, 2023)
The standard pedagogy within Philosophy for Children courses is the community of inquiry. In this paper, I argue that the current form of the community of inquiry does not properly accommodate autistic students. Using observations from Benjamin Lukey alongside my personal testimony, I illustrate how autistic students may struggle within the community of inquiry. Importantly, I argue that this need not be the case, as the community of inquiry can be made more inclusive if it were to emphasize collaboration instead of verbal dialogue.